Live bands factor of customer preference of bars and restaurant - Jimena, Larah; Legarde, Mae.; Lozada, Ma. theresa; Rodillado, Ma. Cheche (2002)
This descriptive study aimed at determining how live bands influenced customer's preference of bars and restaurant within Iloilo City. Specifically, this study sought answers to the following objectives: one, assess the influence of of live bands to customers with regards to their age, allowance or income, civil status, educational attainment and occupation; two, determine the specific qualities in a band that attract customers, and lastly, assess the effects of live bands on the profitability of bars and restaurant. The study was conducted during the second semester of academic year 2001-2002. The respondents of this study were the two-hundred ten (210) purposively selected individuals who were made to answer a questionnaire consisted of ten (10) items that provided information regarding the respondents's choice of bars and restaurant that hired live bands, qualities in aa band and the type of music they preferred, customer's attitude towards spending for a night-out and other matters. There were also five (5) randomly selected respondents from Barracks, Cairo, Calzada, Marina, Quarry and Zuba who were made to answer the survey question. "It is because of the live bands that you prefer to spend the night out?" Interviews with the top management of the above-mentioned bars and restaurant were also made. The statistical tools used in this study were frequency count, percentages and ranking for descriptive statistics and chi-square for inferential statistics. The findings of the study revealed the following: Two third of the respondent who were asked whether it is because of the presence of live bands that they prefer to spend their nigh-out answered "Yes" and most of the managers of bars and restaurants think that the presence of live bands contribute to their profitability, thereby establishing the fact that live bands indeed influence the customer's preference of bars and restaurants. Finding also showed that the influence of live bands on their choice s not really affected by the allowance/income, age, sex, educational attainment and occupation of respondents. The result also showed that Barracks was mostly preferred by respondents as to bars and restaurants with live bands followed by Marina and Calzada respectively. It also showed that customers prefer popular live bands, which were known to deliver good performance. The type of music they wanted to hear according to the survey were rhythm and blues, alternative music and love songs. Findings also revealed that managers of the said bars and restaurants were also aware of the customers' preferences when it comes to live bands. This is the reason why they would willingly pay high just to avail the services of a band, which has already established a name and were known to entertain the crowd.
[Research Paper] (BA 200 - Business Research) -- [Iloilo City : UPV-CM], April 2002.